RISK ASSESSMENT FOR HEALTH OF THE POPULATION FROM AIR POLLUTION BY EMISSIONS OF NOVOKUZNETSK PILOT-PRODUCTION PLANT OF TECHNOLOGICAL EQUIPMENT - Суржиков, Дмитрий Вячеславович; Кислицына, Вера Викторовна; Голиков, Роман Анатольевич; Суржикова, Раушания Нафиловна (Medicine in Kuzbass, 2019)
Subject. The subject of the study is the atmospheric emissions of Novokuznetsk pilot-production plant of technological equipment.Objective – to assess the risk to public health from exposure to atmospheric emissions of Novokuznetsk pilot-production plant of technological equipment.Methods. The assessment of emissions of enterprises was based on the analysis of the volume of maximum permissible emissions. Hazard indices for acute and chronic exposure were determined. The maximum and average annual concentrations of toxic substances from each emission source at each of the points of exposure to concentrations (PEC) of toxic substances related to residential neighborhoods were calculated on the basis of data on the distance between each point and each emission source. Risks to public health were calculated.Main results. The main toxic substances contained in the atmospheric emissions of Novokuznetsk pilot-production plant of technological equipment, namely, diiron trioxide and manganese and its compounds, were determined. The city areas which were the most unfavorable for living were identified. It was shown that the total risk of chronic intoxication was the greatest among the residents of Berezka neighborhood of the Zavodskoy district (PEC № 1), and it was 8.45 × 10-4 (in shares of one). The greatest carcinogenic risk to public health from exposure to ethenylbenzene was identified in PEC № 1 (9.26 ×·10-10). Based on the results of the risk assessment, conclusions were drawn on the impact of emissions from Novokuznetsk pilot-production plant of technological equipment on the health of the population of the city and their contribution to the decrease in the level of residents’ health was estimated.Conclusion. In general, the emissions of Novokuznetsk pilot-production plant of technological equipment do not have a significant impact on the health of the population.
Keywords: industrial enterprise; atmospheric emissions; risk assessment methodology; hazard index; non-carcinogenic risk; carcinogenic risk; toxic substances